Fullerene‐Based Inverted Perovskite Solar Cell: A Key to Achieve Promising, Stable, and Efficient Photovoltaics - Raneen Zahran; Zafer Hawash (Advanced Materials Interfaces)
Abstract Fullerene is one of the most critical materials that are widely used to improve and examine the inverted perovskite solar cells (PSCs, p‐i‐n structure). Fullerenes are known to improve the stability, lower the hysteresis, and increase the power conversion efficiency of the PSCs. Fullerene and its derivatives are often used in constructing effective PSCs. Several properties and performance of fullerenes are the key bases for testing and making effective alternatives that can improve the performance of PSCs. This review summarizes some of the most important fullerenes (i.e., fullerene and its derivatives) that are employed in inverted (p‐i‐n) PSCs and their physical properties that can overcome the well‐known shortcomings in perovskite materials. The current density–voltage hysteresis in PSC and the fullerenes role in lowering the hysteresis are discussed. Moreover, fullerenes are also reviewed as electron transport layer, cathode buffer layer, and additives for perovskites. Enhanced stability by using fullerene derivatives is illustrated. Additionally, fullerenes in flexible and tandem PSCs as well as advantages and disadvantages of fullerenes are briefly discussed. Finally, an overview of the fullerene future in PSCs is discussed with alternative nonfullerene materials used in PSC.